2018
DOI: 10.1002/jemt.23146
|View full text |Cite
|
Sign up to set email alerts
|

Surface characteristics of a modified acidulated phosphate fluoride gel with nano‐hydroxyapatite coating applied on bovine enamel subjected to an erosive environment

Abstract: This study evaluated the antierosive effect applying a modified acidulated phosphate fluoride (APF) gel containing nano-hydroxyapatite (nHAp) on the enamel surface before erosion. After polishing, the exposed flat enamel surfaces (n = 7/group) from bovine incisors were treated with artificial saliva (S -negative control), orange juice (ERO), APF gel (positive control) and APF_nHAp gel. All samples were subjected to six cycles of demineralization (orange juice, pH~3.5, 10 min) followed by remineralization (sali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 45 publications
3
19
1
1
Order By: Relevance
“…18 In the present study the pH of the erosive drink used was 2.8 at a temperature of 10ºC, below to 5.5 and 6.5 that are the critic pH of enamel and dentin, respectively, 19 thus showing that the utilized juice has an acidic pH enough to cause tooth demineralization by increasing the surface roughness at the enamel. It probably occurs because at low pH like that observed for the lemon juice, the amount of H + increases, wakening the binding of Ca +2 ions, leading then into solution, 16 changing the enamel surface by the increasing at the surface roughness, what was observed in this study ( Table 1). Other authors found by SEM images analyses that citric fruit juice caused morphological changes to the enamel surface, including the presence of craters and surface irregularities.…”
Section: Resultssupporting
confidence: 62%
See 3 more Smart Citations
“…18 In the present study the pH of the erosive drink used was 2.8 at a temperature of 10ºC, below to 5.5 and 6.5 that are the critic pH of enamel and dentin, respectively, 19 thus showing that the utilized juice has an acidic pH enough to cause tooth demineralization by increasing the surface roughness at the enamel. It probably occurs because at low pH like that observed for the lemon juice, the amount of H + increases, wakening the binding of Ca +2 ions, leading then into solution, 16 changing the enamel surface by the increasing at the surface roughness, what was observed in this study ( Table 1). Other authors found by SEM images analyses that citric fruit juice caused morphological changes to the enamel surface, including the presence of craters and surface irregularities.…”
Section: Resultssupporting
confidence: 62%
“…14 In addition, bovine incisors are frequently used in dental research due to the difficult to obtain intact human teeth, 15 and its larger surface allow the use of demineralization and remineralization researches. 5,6,8,16,17 In this study it was observed that there was no significant difference in statistical values between the groups of the control region, that indicates that the waterproofing of the specimens with the nail enamel and sticky wax was effective (Table 1). However, in the experimental region of the specimens the values of surface roughness presented statistical similar values between the groups and statistically higher when compared with that obtained at the control region ( Table 1).…”
Section: Resultsmentioning
confidence: 63%
See 2 more Smart Citations
“…In this study, SEM was selected to analyze the effect of the abrasion, erosion, and saliva on enamel and dentin morphology to measure substance loss accurately and provide visual information on surface precipitates and change of the surface morphology. Conversely, μ‐EDXRF provides a specific method to determine the concentration of chemical elements on substratum surfaces, being previously used in some studies in dentistry (De Carvalho Filho et al, ; Gomes et al, , ; Soares et al, ; Soares & De Carvalho Filho, ; Soares, De Oliveira, et al, ; Soares et al, ; Soares et al, ).…”
Section: Discussionmentioning
confidence: 99%